Modeling of inverted pendulum on a cart by using Artificial Neural Networks - Korkmaz, Deniz; Bal, Cafer; Gökbulut, Muammer (Institute of Electrical and Electronics Engineers Inc., 2015)
In this study, mathematical model of the single bar inverted pendulum on a cart, which exhibits similar behavior to the dynamics of a robotic arm, is derived by using Lagrange method. At the same time, nonlinear model of the inverted pendulum is simulated in MATLAB environment by using Multilayer Artificial Neural Networks (MANN). MANN is trained by back propagation learning algorithm and dynamic NARX network model is selected for MANN. This model is the basis for dynamics of the robotic arm. © 2015 IEEE.
Arabali bir ters sarkacin yapay sinir a?lari ile modellenmesi
2015 23rd Signal Processing and Communications Applications Conference, SIU 2015 -- 16 May 2015 through 19 May 2015 -- Malatya -- 113052
Keywords: artificial neural networks; inverted pendulum; lagrange method; nonlinear modeling